PERANCANGAN APLIKASI KOMPETENSI DAN PRESTASI MAHASISWA UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARI - Yusup Indra Wijaya; Muhammad Saidi Rahman (FKOM UNIKU, 2023)
Student achievements are a form of outcomes achieved during their academic activities at a higher education institution. Achievements are one of the essential factors in assessing the quality of an educational institution. One example is the accreditation evaluation of a study program or the assessment of an institution based on student achievements. Currently, the management of student achievement data is still done manually, where each student's academic and non-academic achievements are reported to the Student Affairs department for data recording. Considering the importance of student achievement data, there is a need for a system to facilitate the management of this data by the Student Affairs department. In this system, students who achieve success can directly input their data into the system. When the data is needed, the operator can easily present the required student achievement data. The system is built using PHP programming language and MySQL database, and it has proven to provide convenience to the Student Affairs department in managing student achievement data. With this system in place, study programs are also assisted in accessing student achievement data for accreditation assessment purposes